Does it matter what observers say? The impact of international election monitoring on legitimacy. Issue 1 (1st January 2022) - Benstead, Lindsay; Kao, Kristen; Lust, Ellen
ABSTRACT: Scholars and democracy promoters often suggest that electoral observers' (EOs') assessments impact public opinion in a straightforward manner, yet, research on communication cautions against these sanguine assumptions. We test the impact of EO statements on public opinion in two very different contexts using survey experiments conducted among 3, 361 Jordanians and Tunisians. Our results demonstrate the need for democracy promoters to consider negative consequences when implementing democracy promotion programmes, and for scholars to undertake further research regarding the impacts of election monitoring on domestic attitudes.